Growth, Bone Health, and Cognition: Nutritional Evaluation of a Sustainable Ocean-Based Advance Protein Powder (APP). Issue 2 (4th March 2019) - Wong, Carmen P.; Bray, Tammy M.; Khanna, Sunil K.
ABSTRACT: This study evaluated an alternative ocean-based fish protein, Advanced Protein Powder (APP) as a feasible, environmentally sustainable protein source to reduce childhood malnutrition. We completed a rodent feeding study to evaluate growth and development in young growing mice on a purified diet containing APP as compared to mice-fed diets using other common protein sources – casein, whey, and soy. Results suggested APP to be an effective and safe protein source and ensured normal body growth, bone development, and brain function in APP diet-fed mice. Evidence provided in this study supports considering the use of APP to reduce malnutrition among children worldwide.